(5y+1)(7-y)=0

Simple and best practice solution for (5y+1)(7-y)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5y+1)(7-y)=0 equation:



(5y+1)(7-y)=0
We add all the numbers together, and all the variables
(5y+1)(-1y+7)=0
We multiply parentheses ..
(-5y^2+35y-1y+7)=0
We get rid of parentheses
-5y^2+35y-1y+7=0
We add all the numbers together, and all the variables
-5y^2+34y+7=0
a = -5; b = 34; c = +7;
Δ = b2-4ac
Δ = 342-4·(-5)·7
Δ = 1296
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1296}=36$
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(34)-36}{2*-5}=\frac{-70}{-10} =+7 $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(34)+36}{2*-5}=\frac{2}{-10} =-1/5 $

See similar equations:

| 7^3x-4=49 | | 10=1-5x | | (5z+1)(9+z)=0 | | 3m+3m=18 | | 2x+10+x=-x-8-4x+2 | | 1/9y-6=-19 | | 6w-3w+2w=20 | | 6.78j-(5.2)=4.33j+2.15 | | 8-6x=x | | 31=4n+11 | | 10x=x-10 | | 16d+3d+d-17d=18 | | y/12+5=-8 | | 43=5j+13 | | 36x19=19x36 | | 15p+4p-7p=-12 | | 30a+.10a=50a | | 1620=45m | | 29=14+u | | 8(4x+7)=32x-1 | | 10q-6q=12 | | 10q-6q=1/ | | 29-29=5(2a-1)=2a | | 11=4+d | | 5j-2j+6j=18 | | 8+4a=6a | | n^2-1n=1482 | | 36=6f+12 | | 182=-8-10p | | 4a+a-3a+2a-3a=6 | | 7m–2=8m+4–m | | 8(x-5)=12(4x-1)+11 |

Equations solver categories